Dilated Cardiomyopathy and Prone Position: An Anesthetic Challenge - Hooda, Bhavna; Sud, Saurabh; Dwivedi, Deepak; Yadav, Sanjay K. (Journal of Neuroanaesthesiology and Critical Care, 2020)
The anesthetic management of a patient with dilated cardiomyopathy (DCM) for noncardiac surgery is challenging due to associated congestive heart failure, malignant dysrhythmias, sudden cardiac arrest, implanted rhythm devices, and thromboembolism. We report successful conduct of a case of DCM on cardiac resynchronization device with Cauda equina syndrome (CES) under general anesthesia in prone position. The anesthetic concerns specific to the pathophysiology of DCM are also discussed.
Keywords: cardiac resynchronization therapy device; dilated cardiomyopathy; prone position